2020
DOI: 10.1177/0893318920912738
|View full text |Cite
|
Sign up to set email alerts
|

Expanding structurational divergence theory by exploring the escalation of incompatible structures to conflict cycles in nursing

Abstract: Intractable workplace conflicts that impede individual and organizational success are common, yet little is understood about how such cycles are formed. Structurational divergence (SD) theory explains intractable conflict cycles resulting from incompatible meaning structures. SD-nexus is the interpenetration of equally compelling but incompatible structures, creating unresolvable conflicts, thus escalating the SD-nexus to the SD-cycle of intractable conflict: unresolvable conflict, immobilization, and erosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Because of this, ECE participants perceived that structural change may not happen; thus, design was useful in highlighting the necessity for other mechanisms (e.g., different voices and people who can advocate and champion change; Nicotera, 2015). Cultures that share similar dynamics to ECE might integrate CAD approaches throughout the educational program to uncover how and why conflicts like D&I are formed and become intractable (Malterud & Nicotera, 2020). CAD provides a unique framework that can simultaneously foster breakthroughs or breakdowns toward managing organizational communication and conflict processes (Galli & Suteu, 2013).…”
Section: Three Theoretical Considerations Of Design In Addressing Wicmentioning
confidence: 99%
“…Because of this, ECE participants perceived that structural change may not happen; thus, design was useful in highlighting the necessity for other mechanisms (e.g., different voices and people who can advocate and champion change; Nicotera, 2015). Cultures that share similar dynamics to ECE might integrate CAD approaches throughout the educational program to uncover how and why conflicts like D&I are formed and become intractable (Malterud & Nicotera, 2020). CAD provides a unique framework that can simultaneously foster breakthroughs or breakdowns toward managing organizational communication and conflict processes (Galli & Suteu, 2013).…”
Section: Three Theoretical Considerations Of Design In Addressing Wicmentioning
confidence: 99%
“…Organizational members experience structurational divergence when they encounter two or more structures that are “equally compelling and contradictory” creating a double-bind, termed as an SD-nexus (Malterud & Nicotera, 2020, p. 385). In short, members experiencing an SD-nexus believe they are “damned if they do, or damned if they don’t” in relation to their organizational action(s) (Nicotera, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an SD-nexus predicts higher rates of employee burnout, role conflict, low job satisfaction, reduced organizational identification, increased turnover, and workplace bullying (Ford et al, 2022; Nicotera et al, 2015). Recently, Malterud and Nicotera (2020) explored communication variables that lead to the escalation of an SD-nexus into an SD conflict cycle. The authors found that as compared to those experiencing an SD-nexus without an accompanying SD-cycle , nurses experiencing an SD-cycle were more likely to “take conflict personally” (TCP; see Nicotera et al, 2015), and engage in a non-confrontational conflict style.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations